RANCANG BANGUN APLIKASI KAMUS DIGITAL FISIKA DENGAN MICROSOFT VISUAL BASIC 6.0 DAN DATABASE MICROSOFT ACCESS 2003 - Dicky Agoeng VP; Eko Risdianto (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Design of Digital Dictionary of Physics Applications using Microsoft Visual Basic 6.0 and Microsoft Access 2003. This Aplication has Aims to generate Physics Simple Dictionary Application using software VB ( Visual Basic ) 6.0 and Database Access 2003 , as well as to determine the feasibility as a source of learning physics . This research is applied research with methods SDLC ( System Development Life Cycle ). Stages of the study includes Planning System , Analysis System , Design System, Implemantasi and Testing System . System testing is done using the application made to the process of learning physics. After that the students who have been administered questionnaire was provided to determine the feasibility of the system 's Dictionary of Digital Physics. Based on the test results of the digital dictionary application feasibility of Physics, found that the percentage of total recapitulation student responses to the feasibility of a digital dictionary of physics is at 95.11 % which is the criteria very well . The total percentage of results indicates that the application 's digital dictionary worthy physics learning tool and as a source of learning physics physics students. Keywords: Digital Dictionary of Physics, Microsoft Visual BAsisc 6.0, Microsoft Access 2003.